Returning and Re-Emigrating Gendered Trajectories of (Re)Integration from Greece - Xhaho, Armela; Erka Çaro (European Journal of Multidisciplinary Studies, 2016)
The aim of this research paper is three fold: (1) to shed some light on the struggles Albanian return migrants are facing in their psycho-social, cultural and labor market reintegration in the origin country, looking as well to the gendered trajectories of return and re-emigration(2) to highlight their gendered strategies in transferring back in their home country their financial, social and human capital;(3) to better understand the dynamic paths of their migration trajectories and finally (4) to push policy makers to put with high priority the returnees reintegration plan into the policy agenda. We base our analyze on 42 life stories of Albanian migrants, from which, 12 interviews with return migrants from Greece, 30 migrants that are actually in Greece (from which 50 percent have at least made an 1 attempt to return in Albania and 5 are circular migrants).The study found that: many Albanian migrants return to Albania to stay either temporary or permanently with the idea of investing in home country, though not all of them who return stay in Albania. Returnees and at a greater degree women, face lot struggles and difficulties in their psycho-social, cultural and economic reintegration upon their return, which make them mentally and psychologically vulnerable. Women experienced a sense of disempowerment, reconfiguration and re-traditionalisation of gender relationships upon their return. Labor market integration seem more problematic especially for returned women who faced a gendered gap in labor force participation . Moreover, despite migrant willingness to invest their financial and social remittances in Albania by bringing new ideas in the labor market trend, they experience a sense of disillusion. Therefore, having no support system back home, remaining jobless and in many cases failing in their investment endeavors, make returnees consider further re-emigration as a surviving strategy. This study suggest that it is time for policy makers to compile with high priority and with a gender lens analysis a new National Migration Strategy and Return Reintegration strategy, while developing concrete and coherent measures upon returnees successful reintegration in the home country. This policy research brings at the policy agenda an holistic and multidisciplinary approach to returnee reintegration through better multi- level/stakeholder collaboration and dialogue.